THE EFFECT OF COARSE AGGREGATE RATIO ON THE PROPERTIES OF NO FINE LIGHT WEIGHT CONCRETE (Journal of Engineering, 2009)
The main object of this work is to study the effect of coarse aggregate/cement ratio (A/C) on the property of no fine concrete. In this work, three ratio of A/C were used (6, 9 and 12 by weight).The cement content is maintained constant (125kg/m3) while the w/c ratio ranges from (0.39 to 0.55 by weight). Tests are carried out on hardened concrete to investigate the effect of coarse aggregate/cement ratio on the compressive strength, absorption%, density, porosity%, ultrasonic pulse velocity, acoustic impedance of mixes.The results showed that increasing the percentage of A/C ratio by weight from 6 to 12 for the used mixes reduces the compressive strength, ultrasonic pulse velocity and acoustic impedance, on the other hand the porosity and the absorption percentage, increase with increasing ratio of A/C for all studied mixes.At 28 days the compressive strength , ultrasonic pulse velocity and acoustic impedance tests with A/C ratio of (12) are (2.8.MPa), (2km/sec) and (3×106 Kg/(sec.m2)) respectively while decreasing the ratio to (6) improves these properties to (9.3MPa), (3km/sec) and ( 5.7 ×106 Kg/(sec.m2)) respectively On the other hand the porosity and the absorption % decrease with decreasing the ratio of A/C for all studied mixes . At 28 days the porosity and the absorption % with A/C ratio of (12) are (40%) and (2.7%) respectively with decreasing the ratio to 6 decrease these properties to (19%) and (1%) respectively.The densities of the mixes were tested. At 28 days the density with A/C ratio of (12) are (1512 kg/m3 )with decreasing the ratio to 6 increase the density to(1907 kg/m3 )Based on the analysis of experimental results, several graphs and tables have been prepared to study the properties of no fine concrete